Studi Penerapan Metode Island Operation Sebagai Defence Scheme Pada Gardu Induk Teluk Lembu - Muhamad Al Khausar; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Sumatra island has 3 interconnecting transmission lines of 150 kV are in the North Sumatra, Sumatra central and southern Sumatra. Teluk Lembu substation is a substation that is connected to the 150 kV Interconnection System Central Sumatra.Blackout is a disruption of the 150 kV transmission system which caused a total blackout. In order to overcome such interference, when the blackout substation Teluk Lembu can secede from the 150 kV interconnection system (Island Operation). Where Power-generator which is connected to the Teluk Lembu substation only supply power to Teluk Lembu substations.Keywords : Teluk Lembu Power plant, Teluk Lembu substation, Blackout, Island Operation.